Implants P-65853023-398 Stepwise drilling protocol in dental implants for patients with low bone densities: Case report. (February 2023) - Solano, N.; Castrillo, A.; Peraza, A.; Rivera, E.; Fuenmayor, L.
Abstract : Purpose: To describe a stepwise drilling protocol for the placement of dental implants that allow achieving ideal primary stability and subsequent prosthetic rehabilitation. Methods: A 62-year-old male patient, who came to the clinic with a chief complaint of partial maxillomandibular edentulism. A CBTC was requested, where bone densities between D3 and D4 were evidenced. Digital planning was carried out using the NemoScan program for the placement of twelve dental implants, six in the upper jaw and six in the lower jaw, using the sequence of conventional drills and the stepwise protocol, which consists of using, after the initial drill of the same length as the implant, the following drills in ascending diameters with a shorter length than the previous drill, allowing better primary stability to be achieved. Results: After the placement of the implants, torques between 50 and 60 N/cm in the mandible and 30 and 55 N/cm in the maxilla were obtained. Provisional prosthesis was installed. In the control at 4 months, a correct osseointegration was evidenced, without clinical evidence of peri-implantitis. Conclusions: When dental implants are placed in areas where low bone densities are present the success of the surgery and the survival of the implant with conventional drilling can be compromised. A good selection of the drill protocol to be used must be made and adequate planning of the case must be carried out. The stepwise drilling protocol represents a good treatment option to increase primary stability in low bone densities, with a high percentage of predictability.